A study on industrial communication networking: ethernet based implementation - Hashim, Hairulazwan (2006)
Recent enhancement of an industrial communication and networking technology has made it possible to apply Ethernet networks at all levels of industrial automation, especially at controller level where the data exchange in real-time communication is mandatory. This thesis presents a study on the development of industrial communication network based on the Ethernet and its implementation on a Computer Integrated Manufacturing (CIM-70A) system which located at Robotic Laboratory in KUiTTHO. The Ethernet module was installed on supervisory OMRON PLC to integrate the various stations in the ClM-70A system. The workability of this communication technique was analyzed and compared with the conventional serial communication which is widely used in automation networking systems. Through this approach, the communication and integration of elM systems can be accessed easily and hence available to be upgraded to the management and enterprise levels of automation.